(untitled) (Journal of research in medical and health sciences, 2026)
Tumor biological markers are characteristic bioactive substances that are either directly synthesized and secreted by abnormally proliferating tumor cells or released by the host in response to oncogenic biological behaviors during the initiation and progression of malignant tumors. These markers play an irreplaceable role in critical clinical scenarios such as cancer screening, therapeutic efficacy evaluation, and prognosis prediction. This article systematically reviews the biological characteristics, classification systems, and latest advances in detection technologies of tumor markers, with emphasis on their performance limits and clinical bottlenecks in early cancer screening. Furthermore, it analyzes emerging trends in the integration of multimodal detection technologies, providing a theoretical reference for precision oncology practice.